PENANAMAN KARAKTER CINTA TANAH AIR MELALUI KEGIATAN EKSTRAKURIKULER KARAWITAN DI SD NEGERI GAMOL SLEMAN - Dyah Ayu Nugrahaningsih; Sri Tutur Martaningsih (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2021)
One of the character crises among students is the love of the country. Cultivating the character of love for the country in schools can be done in various ways, one of which is through musical extracurricular activities or Karawitan extracuricullar. Through musical or Karawitan extracurricular activities, students are expected to be able to love customs and culture, tolerance among others, and love local products, and be able to preserve customs and cultural heritage. This study aims to describe the strategy of cultivating the character of love for the country through extracurricular activities at SD Negeri Gamol Sleman, its inhibiting and supporting factors. This research is a qualitative research. Methods of data using observation, interviews, equipped with documentation. Test the validity of the data using triangulation of sources and techniques. Data analysis was carried out through the stages of data reduction, data presentation, and data collection. The results showed that: 1) The musical or Karawitan extracurricular activities at SD Gamol Sleman involve good cooperation between the principal, teachers of musical or Karawiran extracurricular activities, and students. Extra-curricular implementation includes curriculum components, material approaches, methods, evaluation, and the facilities and infrastructure used; 2) The strategy of cultivating the character of love for the country through musical or Karawitan extracurricular activities at SD Gamol Sleman is carried out in three stages, namely (Knowing Morals), (Moral Loving), (Moral doing); 3) Inhibiting factors are not overlooked and do not hinder activities. The supporting factors in terms of complete musical instruments and support from school residents or the school environment 4) The character of love for the country that is instilled through extracurricular activities for Gamol, including customs and culture, tolerance of others, and love for local product.